2020
DOI: 10.3389/fimmu.2020.570195
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 Plays a Role in Matrix Stiffness-Induced Macrophage Polarization

Abstract: Phenotypic polarization of macrophages is deemed essential in innate immunity and various pathophysiological conditions. We have now determined key aspects of the molecular mechanism by which mechanical cues regulate macrophage polarization. We show that Transient Receptor Potential Vanilloid 4 (TRPV4), a mechanosensitive ion channel, mediates substrate stiffness-induced macrophage polarization. Using atomic force microscopy, we showed that genetic ablation of TRPV4 function abrogated fibrosis-induced matrix s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 68 publications
(168 reference statements)
3
52
0
Order By: Relevance
“…Additionally, it has been shown that cultivation of THP-1 derived macrophages on stiff surfaces increases the expression of M2-markers compared to culture on softer surfaces (130). However, other studies have shown that macrophages can also upregulate the expression of M1-markers when cultured on stiff surfaces (131)(132)(133). The opposing results could be due to the different range of stiffness, type of coating, cell types, and stimulation used.…”
Section: Collagen-mediated Regulation Of the Immune Suppressive Activity Of Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has been shown that cultivation of THP-1 derived macrophages on stiff surfaces increases the expression of M2-markers compared to culture on softer surfaces (130). However, other studies have shown that macrophages can also upregulate the expression of M1-markers when cultured on stiff surfaces (131)(132)(133). The opposing results could be due to the different range of stiffness, type of coating, cell types, and stimulation used.…”
Section: Collagen-mediated Regulation Of the Immune Suppressive Activity Of Macrophagesmentioning
confidence: 99%
“…They found that pulmonary macrophages isolated from patients with idiopathic pulmonary fibrosis acquired a more M2-like phenotype when cultured on various types of collagen compared to pulmonary macrophages isolated from healthy donors ( 134 ). The mechanosensing ability of macrophages has been suggested to involve the ion channel transient receptor potential cation channel subfamily V member 4 (TRPV4) ( 128 , 132 ) and the transcriptional coactivator YAP ( 135 ).…”
Section: Collagen Can Affect the Immune Environment In Tumorsmentioning
confidence: 99%
“…Consequently, modulating receptor engagement by modulating implant surfaces affects the ability of macrophages to attach and spread on surfaces [ 144 ] and to fuse into FBGCs [ 138 , 139 , 145 ]. In addition to integrins and RhoA/ROCK signaling [ 146 ], transient receptor potential vanilloid 4 (TRPV4) channels appear to be critical in mediating macrophage responses and polarization on differently stiff substrates [ 147 ] and macrophage fusion in a Rac1-dependent manner [ 148 ].…”
Section: Implant Surfaces From the Perspective Of A Macrophagementioning
confidence: 99%
“…TRPV4 activation is associated with phenotypic switch by macrophages ( 12 , 13 , 17 , 51 , 94 ). Current understanding of macrophage polarization is based largely on the use of biochemical cues such as cytokines or LPS to alter cellular phenotype.…”
Section: Trpv4 Activity Influences Macrophage Polarization and Metabolismmentioning
confidence: 99%